Effects of wildfire on soils: field studies and modelling on induced underground temperature variations - Chicco, Jessica Maria; Mandrone, Giuseppe; Vacha, Damiano (Frontiers in Earth Science, 2023)
Wildfire statistics report an increasing number of deaths, damages, and force society to face exceptional repair costs also due to secondary effects such as landslides, soils erosion and water quality problems. Literature agrees that the extent of the thermal disturbance of the soil due to wildfire, is strongly dependent on fire intensity, on its duration and recurrence, as well as on fuel load, and soil properties. The unpredictability of these phenomena is one of the main challenges for scientists trying to study their characteristics. Degradation of the biological, chemical, and physical properties of forest soils due to the wildfires can reduce their capacity to function fully, with such effects either temporary or permanent. These factors together with high temperature which can develop in the ground (> 100 °C), causing direct measures in the subsurface can be difficult to obtain.In this article, controlled fires reproducing real conditions of wildfire affecting the Susa Valley (NW Italy) in 2017, which induced intense erosion and debris flows, have been monitored both above and below the ground surface. Moreover, numerical simulations based on real data increased the knowhow to reproduce real changes on the underground. The small-scale fire simulations have allowed to verify how the depth affected by significant increases in temperatures is truly pellicular. Field tests show that at -2 cm depth temperature never exceed 70°C, meaning that it usually does not affect soil components or properties.